The Power of Passionate Teaching and Learning: A Study of Impacts on Social Science Teacher Retention and Student Outcomes - Levitt, Greg; Grubaugh, Steven; Maderick, Joseph; Deever, Donald (Technium Social Sciences Journal, 2023)
Social science teachers play a crucial role in shaping students' understanding of the world and their place within it. They not only impart knowledge but also help students develop critical thinking skills, empathy, and a sense of civic responsibility. Passionate teaching and learning are critical elements of effective education. This paper examines the impact of passionate teaching on teacher retention and wellness, as well as student learning, achievement, and well-being. Passionate teachers are defined by their enthusiasm, engagement, creativity, commitment, and flexibility, and have a positive impact on student motivation and engagement. On the other hand, passionate learners exhibit persistence, creativity, and autonomy in their learning journey. The paper also discusses strategies for increasing teacher passion for teaching, including professional development and a supportive school culture, and fostering student passion for learning, including a positive and engaging learning environment and opportunities for autonomy. The results of this study suggest that enhancing both teacher and student passion has a positive impact on teacher retention, teacher well-being, student achievement, and student well-being.